When Little Things Mean a Lot: On the Inefficiency of Item-Pricing Laws - Mark Bergen; Daniel Levy; Sourav Ray; Paul H. Rubin; Benjamin Zeliger (Journal of Law and Economics, 2008)
Item-pricing laws (IPLs) require a price tag on every item sold by a retailer. We study IPLs and assess their efficiency by quantifying their costs and comparing them to previously documented benefits. On the cost side, we posit that IPLs should lead to higher prices because they increase the costs of pricing and price adjustment. We test this prediction using data collected from large supermarket chains in the tri-state area of New York, New Jersey, and Connecticut. We find that IPL store prices are higher by about 20–25 per item on average. As a control, we use data from stores that use electronic shelf labels and find that their prices fall between IPL and no-IPL store prices. We compare the costs of IPLs to existing measures of the benefits and find that the costs are an order of magnitude higher than the upper bound of the estimated benefits.
Keywords: K20; L11; L81; E31; 330; Item Pricing Law; Cost of Item Pricing Law; Cost of Price Adjustment; Menu Cost; Retail Pricing